Whole-exome sequencing is a powerful approach for establishing the etiological diagnosis in patients with intellectual disability and microcephaly. Issue 1 (December 2015) - Rump, Patrick; Jazayeri, Omid; van Dijk-Bos, Krista; Johansson, Lennart; van Essen, Anthonie; Verheij, Johanna; Veenstra-Knol, Hermine; Redeker, Egbert; Mannens, Marcel; Swertz, Morris; Alizadeh, Behrooz; van Ravenswaaij-Arts, Conny; et al.
Abstract Background Clinical and genetic heterogeneity in monogenetic disorders represents a major diagnostic challenge. Although the presence of particular clinical features may aid in identifying a specific cause in some cases, the majority of patients remain undiagnosed. Here, we investigated the utility of whole-exome sequencing as a diagnostic approach for establishing a molecular diagnosis in a highly heterogeneous group of patients with varied intellectual disability and microcephaly. Methods Whole-exome sequencing was performed in 38 patients, including three sib-pairs, in addition to or in parallel with genetic analyses that were performed during the diagnostic work-up of the study participants. Results In ten out of these 35 families (29 %), we found mutations in genes already known to be related to a disorder in which microcephaly is a main feature. Two unrelated patients had mutations in theASPM gene. In seven other patients we found mutations inRAB3GAP1, RNASEH2B, KIF11, ERCC8, CASK, DYRK1A andBRCA2 . In one of the sib-pairs, mutations were found in theRTTN gene. Mutations were present in seven out of our ten families with an established etiological diagnosis with recessive inheritance. Conclusions We demonstrate that whole-exome sequencing is a powerful tool for the diagnostic evaluation of patients with highly heterogeneous neurodevelopmental disorders such as intellectual disability with microcephaly. Our results confirm that autosomal recessive disorders are highly prevalent among patients with microcephaly.